PENGGUNAAN ALAT HERBST PADA MALOKLUSI KLAS II DENGAN MANDIBULA RETROGNATHI (TINJAUAN PUSTAKA) - Adityo Widodo; Ines Nisa Khairi; Nia Ayu Ismaniati (Faculty of Dentistry, Universitas Indonesia, 2015)
In Orthodontics, functional appliance can be used as a preliminary appliance in treating class II malocclusion with retruded mandible. This type of removable appliance needs patient's full cooperation. However, there is one type of fixed functional appliance known as : Herbst Appliance, which was introduced by Herbst in 1909 and redeveloped by Panchers in 1979. By using this appliance, the treatment period is much shorter compared to that of other removable functional appliances and results is more effective. This telescopic mechanism principle produces posterior forces to maxillary dentoalveolar complex and anterior forces to mandibular dentoalveolar complex. The expected effect of the treatment is longer mandible, distal movement of upper molars, mesial movement of lower molars, higher vertical dimension and a decrease of profile convexity. Based on those facts, in treating class II malocclusion -division I or II - a Herbst appliance might be taken into consideration.